2001
DOI: 10.2355/isijinternational.41.25
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Dimensional Change, and Its Dispersion, on the Fabrication Size Tolerances of Austempered Ductile lron (ADI) Parts. Comparison with SAE 4140 Steel.

Abstract: To accurately satisfy the size tolerance of metallic parts, it is necessary to take into account the dimensional change (DC ) caused by heat treatment, and the dispersion (DDC ) of the DC values. The information available on this topic for ADI is very scarce.The present work aims to determine DC and DDC on ADI and SAE 4140 steel parts and to analyze its influence on the size tolerances. Ductile iron and SAE 4140 steel specimens were used to compare DC and DDC caused by austempering, and quenching and tempering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The studies carried out by Moncada and Sikora (1996) have demonstrated that DC of conventional sized ADI parts mainly depend on heat treatment parameters and prior microstructure. Echeverría et al (2001) agree with this results working on ADI parts of thickness ranging from 10 to 40 mm. Nevertheless, to the best of the authors' knowledge RS, DC, distortion and surface hardening have not been reported for ADI parts of small thickness.…”
Section: Introductionsupporting
confidence: 93%
“…The studies carried out by Moncada and Sikora (1996) have demonstrated that DC of conventional sized ADI parts mainly depend on heat treatment parameters and prior microstructure. Echeverría et al (2001) agree with this results working on ADI parts of thickness ranging from 10 to 40 mm. Nevertheless, to the best of the authors' knowledge RS, DC, distortion and surface hardening have not been reported for ADI parts of small thickness.…”
Section: Introductionsupporting
confidence: 93%
“…These can lead to the formation of elastic strains, which cause: a) heavy microstructural subsurface damage because of the graphite matrix interfaces and debonding, matrix microcracking, and void growth, b) a significant amount of austenite-martensite transformation, and c) decomposition of the reacted stable austenite, due to the localized increase in temperatures. [16][17][18][19][20] The reacted austenite matrix in ausferrite is thermodynamically stable down to liquid nitrogen temperatures. During the heating process, acicular ferrites in bainitic ductile cast iron break and the reacted austenite phase decomposes to carbide and ferrite.…”
Section: B Results Of Thermal Shock Testmentioning
confidence: 99%
“…Also DCI has high strength and toughness comparable to steel materials. [5][6][7] Furthermore, in the sand mold casting, DCI may reduce the residual stress by cooling gradually. Therefore, the DCI fatigue strength can be improved higher than the fatigue strength of welded structures.…”
Section: Introductionmentioning
confidence: 99%